O papel da cirurgia de descompressão portal e o desenvolvimento de insuficiência hepática no curso evolutivo da esquistossomose hepatoesplênica. - Guilherme Santiago Mendes (2007)
Morbidity and mortality of hepatosplenic schistosomiasis (HSS) are basically determined by portal hypertension and gastrointestinal bleeding due to rupture of esophageal and gastric varices. Based on the classic concept that HSS is a fibrosing condition, which does not affect liver function, the surgical treatments have been considered an efficient and safe option to decompress the portal system, specially by the esophagogastric devascularization with splenectomy (EGDS). Nevertheless, the more appropriate postoperative follow-up haspointed twards some negative aspects related to surgery, particularly a high frequency of portal thrombosis. Moreover, some studies on blood coagulation have shown hepatocellular dysfunction in HSS patients and some experimental investigations have demonstrated thatpoor portal perfusion may influence in the process of fibrogenesis. This study aimed to follow-up, in long-term, a group of 63 HSS patients and, based on clinical, laboratory and echographic parameters, to compare the differences in the evolution of those who underwent (n = 34) or not (n = 29) EGDS. The mean follow-up period was 4.3 (2.0 13.9)years and the mean postoperative period was 22 (3.0 45.0) years. The results showed that HSS presented earlier in the group of individuals submitted to surgery (OP) (p = 0.000), and upper gastrointestinal bleeding (UGIB) was the most frequent initial clinical manifestation in this group. On the other hand, in non-operated individuals (NOP), theinitial manifestations of HSS were more varied and had a later onset. There was no statistically significant difference in the frequency of UGIB between the NOP and OP groups both in the preoperative (p = 0.179) and postoperative (p = 0.114) periods. Most OP patients (65%) had postoperative UGIB and a high frequency of portal thrombosis (71%).Among the NOP patients, the frequency of thrombosis was 10% (p = 0.000, odds ratio = 21). The frequency of post-surgical UGIB was higher in the OP patients who developed postoperative non-recanalized portal thrombosis in relation to those OP ones who did not present any thrombosis (p = 0.028, odds ratio = 9.75). The occurrence of decreased portal flow was similar in both groups (p = 0,799), but the probable determining conditions were different (p = 0.013) portal thrombosis in the OP group (odds ratio = 34.67) and spontaneous portosystemic anastomoses in the NOP group (odds ratio = 35). The frequency of hepatic failure was similar in the two groups (p = 1,000). There was a strong association between occurrence of decreased portal flow and hepatic failure, in both the OP (p = 0.000, odds ratio = 30) and NOP (p = 0.000, odds ratio = 45) groups. These clinical findings led us to argue about the role played by portal system decompression surgery, andto infer that decreased portal flow may have a determining role in the development of hepatic failure during the course of HSS.